IMPLEMENTASI MODEL COOPERATIVE SCRIPT PADA SISWA KELAS VIII A MTsN 3 ACEH BARAT - Rozayani Rozayani (Cross-border, 2019)
The purpose of this study was to improve social studies activities and learning outcomes on population dynamics material through the application of a cooperative script model for class VIII A MTsN 3 West Aceh students. The model used in this study is a cooperative script model. The number of students was 40 students including 22 male students and 18 female students. This research was conducted in a period of 3 months. The method used was classroom action research which consisted of two cycles and each cycle consisted of two meetings. Each cycle consists of planning, implementing action and reflection. The research procedure in the first cycle, namely pre-research, planning, action implementation, observation and reflection. In the second cycle, namely planning, implementing actions, observing and reflecting. Research data comes from test scores at the end of each learning cycle for each cycle plus observation data on student activity in the learning process. Furthermore, the data were analyzed statistically percentage. The results showed that there was an increase in the mastery of student learning outcomes from 37.50% in the pre-study to 65.20% in the first cycle and increased again to 80.00% in the second cycle. The increase in student activity in the learning process was from 72.50% in the first cycle, and increased again to 87.50% in the second cycle. The implementation of the cooperative script model can improve social studies activities and learning outcomes in the population dynamics material for class VIII A MTsN 3 West Aceh.